Brief history of bioinformatics (2008)
Bioinformatics appears as the result of the indissoluble marriage between informatics technology and life sciences. Although it was conceived in principle to resolve questions such as the following: How to store and organize DNA sequences? How to find introns and exons in genomic DNA sequences? What conditions are required for the transcription of a specific gene? How learn more about the structure of a protein? How does it compare sequences of proteins or predict their structures?, currently the acquisition of new and improved computational tools has made it possible that bioinformatics will be key piece in applications such as genetic screening, molecular diagnosis, drug discovery and crop genetic improvement. © 2008 Corporación Editora Médica del Valle.